The efficacy of road safety education to prevent pedestrian fatalities in Limpopo Province (South Africa) - Modipa, Mmakwena; Kockott, Sean; Olutola, Adewale (Technium Social Sciences Journal, 2022)
This paper explores road safety education to prevent pedestrian fatalities in Limpopo Province. Pedestrian safety remains one of the main challenges for road safety authorities as many road users are losing their lives on the road. The inability of both pedestrians and motorists to understand and interpret the rules of the road is a major problem in Limpopo Province. The study utilised quantitative approach. The sample consisted of 195 respondents. Comprises of 15 civil engineering companies, 23 civil society organisations, 52 community members, 51 teachers and 54 traffic police officials. The findings from the study revealed among many others, that 64.1% of respondents agreed that non-involvement of parents in road safety education contribute to pedestrian fatalities; 61% of the respondents agreed that ineffective scholar patrol contribute to pedestrian fatalities; 67.2% of the respondents agreed that lack of professional support in road safety contribute to pedestrian fatalities and 72% of the respondents agreed that limited resources in road safety contribute to pedestrian fatalities. Based on the findings, the author provided, possible recommendations such as; Department of Transport and Education should involve parents/guardians in road safety education; Department of Education should review scholar patrol to ensure that it assist positively in preventing pedestrian fatalities; Traffic authorities should partner with academics to provide road safety policies and strategies; Department of Transport should partner with private sector to provide resources for road safety education in Limpopo Province.